Endoplasmic reticulum stress regulates pyroptosis in BPDE‐induced BEAS‐2B cells. Issue 7 (16th March 2022) - Zhang, Qiao; He, Xi; Yu, Qi; Liu, Yitong; Zhu, Yonghang; Yang, Liu; Shang, Pingping; Zhang, Jiatong; Liu, Hong; Feng, Feifei
Abstract: Benzo(a)pyrene(B(a)P), as the main representative of polycyclic aromatic hydrocarbons, can promote inflammation and many chronic pulmonary diseases. However, the underlying mechanism of Benzo(a)pyrene‐7, 8‐diol‐9, 10‐epoxide (BPDE)‐induced human bronchial epithelial cell pyroptosis related to endoplasmic reticulum stress (ERS) has not been elucidated. This study focused on the effects of BPDE on ERS and pyroptosis in human bronchial epithelial cells (BEAS‐2B), and explored the relationship between ERS and pyroptosis. BEAS‐2B cells were stimulated with 0.50, 0.75, and 1.00 μmol/L BPDE for 24 h to detect ERS and pyroptosis. After inhibition of ERS with 4‐phenylbutyrate (4‐PBA), pyroptosis of BEAS‐2B cells was tested. The results showed that BPDE decreased the cell viability, changed the morphological structure of endoplasmic reticulum and increased the expression levels of GRP78 and p‐PERK. After BPDE treatment, the cell membrane was damaged and incomplete under transmission electron microscope; Hoechst 33342/PI fluorescence staining showed that the number of PI‐positive cells was enhanced. The expression levels of GSDMD‐N, cleaved‐caspase 1, and cleaved‐IL‐1β were elevated, and the expression levels of IL‐1β, IL‐18, and NLRP3 protein were improved. In BPDE combined with 4‐PBA intervention group, the rate of PI‐positive cells was reduced, the expression levels of GRP78, GSDMD‐N, and cleaved‐caspase 1 were decreased, and the expression levels of IL‐1β, IL‐18, and NLRP3 were decreased. In conclusion, BPDE could induce ERS and pyroptosis in BEAS‐2B cells, and ERS may promote the occurrence of BPDE‐induced pyroptosis.